Business strategies and organizational performance: Unveiling the mediating role of competitive advantage - Al-Ariqi, Sama; Alhakimi, Wail (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the study is to investigate how competitive advantage influences the relationship between business strategies and organizational performance in higher education institutions. The data were gathered from 309 academic and administrative leaders via a structured survey using a quantitative research methodology. SmartPLS 4 was used for data analysis in the study. The cost leadership, differentiation, and focus strategies are business strategies that have a positive impact on organizational performance both directly and indirectly through competitive advantage, according to the findings. To improve university performance, strategic decision-making is essential. By combining market-based and resource-based views with Porter's generic strategies model and the Balanced Scorecard framework, the study adds to the body of knowledge on strategic management. In practice, the results provide insight to legislators and university administrators on how to improve competitive positioning, enhance strategic planning, and enhance organizational performance in a changing educational environment.